Comparison of Increasing Efficiency in DAB Converters using EPS, DPS and TPS with Evolutionary Algorithms - Esturk, Akiner; Akboy, Erdem (IEEE, 2023)
Dual Active Bridge (DAB) converters are widely used in energy storage systems and electrical vehicle applications due to providing isolation and bidirectional power flow. However, recycling energy causes additional losses and minimum efficiency. So, there are phase shift control techniques to minimize recycling energy and increase efficiency. In this paper, nature-inspired evolutionary algorithms which are Genetic Algorithm (GA) and Particle Swarm Optimization (PSO) are used to determine the optimum phase shift ratios in search space.
Keywords: Dual Active Bridge Converter; Multi Objective Optimization; Optimization Algorithm; Genetic Algorithm; Energy & Fuels; Engineering